Development Studies: E-Module Based on Ethnomathematics to Improve Problem-Solving Ability at Junior High School10 Metro - Lita, Rahma Nur; Mustika, Juitaning (IndoMath: Indonesia Mathematics Education, 2024)
There are still many students who need help solving mathematical- problems. The need for attractive, easy-to-understand, and culture-based learning is essential for students. The objectives of this research are as follows: 1) to determine the stages of development of ethnomathematics-based e-modules, and 2) to find out whether ethnomathematics-based e-modules can improve problem-solving abilities at state junior high school 10 Metro. The research method uses a design research and development study type, including preliminary and prototyping stages (formative evaluation). According to the subject matter, media, and cultural experts, it is "highly feasible". Suggestions and comments from revised validators display feasibility. Meanwhile, the attractiveness of the e-module is evident in how students effectively use it. The results of the N-gain value analysis with an average of 0.8 indicates that ethnomathematics-based e-modules can significantly improve students' problem-solving abilities with high criteria. The e-module has met the criteria as a suitable medium for learning.